Códigos lineares disjuntos e corpos de funções algébricas - Silva, Pryscilla dos Santos Ferreira (2011)
In this work, based on algebraic function fields, we give constructions of disjoint linear codes. In addition,we study the asymptotic behavior of disjoint linear codes from our constructions.